La doctrina del derecho natural y el positivismo jurídico - Kelsen, Hans (2008)
"Originally published in Revista Jurídica de Buenos Aires, no. IV, Buenos Aires, Department of Publications, Faculty of Law and Social Sciences, University of Buenos Aires, 1961, pp. 9-45. Translation by Eugenio Bulygin."